PENGARUH KEPEMIMPINAN DAN DISIPLIN TERHADAP KOMITMEN PENCAPAIAN KINERJA SUMBER DAYA MANUSIA - Dewi, Nuning Nurna; Rodli, Ach. Fathoni (Managere: Indonesian Journal of Educational Management, 2021)
This study aims to conduct a study on the influence of principal leadership and teacher discipline on commitment to achievement of teacher performance in UPT Pendidikan, Manding District, Sumenep Regency. The population in this study were all school principals and elementary school teachers in the Manding sub-district, Sumenep Regency, while the sample in the study was taken a number of 40 who were taken randomly. The data analysis used in this research is regression analysis. Based on the data analysis conducted, the following conclusions are obtained: 1) because tcount> ttable or 2.14> 2.02, there is a positive and significant influence of leadership (X1) on teacher commitment and performance (Y) if the influence of school discipline (X2) fixed, 2) because tcount> ttable or 10.25> 2.02, then there is a positive and significant influence of leadership (X2) on teacher commitment and performance (Y) if the influence of school discipline (X1) is constant, 3) because tcount > ttable or 7.52> 2.02, then there is a positive and significant influence of leadership (X1) and discipline (X2) on the commitment to achieving teacher performance (Y).